Architecting software intensive systems : a practitioner's guide - Lattanze, Anthony J. (CRC Press, 2009)
Focusing on the architecture centric design method (ACDM), this book provides deep insight into designing software architectures for systems and how to effectively use architectural design artifacts once created. The text describes how to integrate ACDM with existing organizational structures and processes. The author demonstrates how to tailor defined software process frameworks and methodologies to ACDM in order to design the architecture for a software intensive system. The chapters offer practical guidelines for the general iterative model, the general waterfall model, the rational unified process, the team software process, scrum, as well as extreme programming.